A revision of Hoplasoma acuminatum and H. thailandicum species groups, and re-definition of H. unicolor species group (Coleoptera: Chrysomelidae: Galerucinae) - Bezděk, Jan (Zootaxa, 2014)
Two species groups within the genus Hoplasoma Jacoby, 1884 are defined and revised. The Hoplasoma acuminatum species group is established for H. acuminatum Medvedev, 2000 and H. sumatranum Medvedev, 2000, and the Hoplasoma thailandicum species group for H. thailandicum Kimoto, 1989; H. vithala sp. nov. (Vietnam, Laos, Thailand) and H. andrewesi sp. nov. (Myanmar). Hoplasoma unicolor species group is re-defined. The male of H. acuminatum, to date unknown, is described. Colour photo of habitus and both male and female genitalia are provided for all the species revised. The checklist of all species currently classified in Hoplasoma is provided.